Pengelolaan Celebrity Endorsement dalam Pengembangan Brand Awareness pada Online Shop Iphone by Sheila - Salma Dhiya Fatharani Wibawa; Ani Yuningsih (Bandung Conference Series: Public Relations, 2024)
Abstract. The rapid development of the digital era forces business people to adapt their marketing strategies to the online realm. Celebrity endorsements have become a prominent strategy in a competitive marketing environment, because the messages conveyed by celebrities via social media have proven to be effective in increasing brand awareness. This research focuses on Iphone by Sheila, a store that has shown rapid growth in two years. The aim of this research is to analyze the implementation of management functions in the form of POAC (Planning, Organizing, Actuating and Controlling) by Iphone by Sheila. This research uses a qualitative method with a descriptive case study approach. The research results show that the celebrity endorsement management implemented by Iphone by Sheila has succeeded in accelerating the increase in brand awareness by utilizing various social media platforms, especially Instagram. Through selecting the right celebrities and good social media management, Iphone by Sheila is able to build trust and long-term relationships with customers. This research underscores the importance of adapting marketing strategies in the digital era and provides practical insights for other businesses looking to increase brand awareness through celebrity endorsements. Abstrak. Perkembangan era digital yang pesat memaksa para pebisnis untuk menyesuaikan strategi pemasarannya ke ranah online. Celebrity endorsement menjadi salah satu strategi yang menonjol dalam lingkungan pemasaran yang kompetitif, karena pesan yang disampaikan oleh selebriti melalui media sosial terbukti efektif dalam meningkatkan brand awareness. Penelitian ini berfokus pada Iphone by Sheila, sebuah toko yang menunjukkan perkembangan pesat dalam dua tahun. Tujuan dari penelitian ini untuk menganalisis implementasi fungsi manajemen berupa POAC (Planning, Organizing, Actuating, dan Controlling) oleh Iphone by Sheila. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus yang bersifat deskriptif. Hasil penelitian menunjukkan bahwa pengelolaan celebrity endorsement yang diterapkan oleh Iphone by Sheila berhasil mempercepat peningkatan brand awareness dengan memanfaatkan berbagai platform media sosial, terutama Instagram. Melalui pemilihan selebriti yang tepat dan pengelolaan media sosial yang baik, Iphone by Sheila mampu membangun kepercayaan dan hubungan jangka panjang dengan pelanggan. Penelitian ini menggarisbawahi pentingnya adaptasi strategi pemasaran dalam era digital dan memberikan wawasan praktis bagi bisnis lain yang ingin meningkatkan brand awareness melalui celebrity endorsement.